1987
DOI: 10.1128/aem.53.8.1969-1972.1987
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacy of the Eucaryote Inhibitor Cycloheximide in Studies of Protozoan Grazing on Bacteria at the Freshwater-Sediment Interface

Abstract: Four guilds from a lake sediment-water interface microbial community were isolated and tested for sensitivity to cycloheximide (0.1 to 200 mg liter-1). Field experiments were conducted to compare the inhibition, dilution, and filtration methods for determining grazing rates. Cycloheximide inhibited anaerobic bacteria at 50 mg liter-', and inhibition of bacterial growth was observed in the grazing experiments. The results show that the assumption of selective inhibition of heterotrophic eucaryotes was violated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Cycloheximide, as a eukaryote-specific inhibitor, has been commonly used in studying protozoan predation (Taylor & Pace, 1987). The most commonly used inhibitory concentration is 100 mg L À1 (Sanders & Porter, 1986), while various concentration ranges, for example 25-200 mg L À1 (Tremaine & Mills, 1987), were reported to be effective in inhibiting protozoa. Much higher concentrations of cycloheximide were used previously in sediment studies (Davies et al, 1995), presumably to counter the adsorption of cycloheximide by organic matter in sediment.…”
Section: Discussionmentioning
confidence: 99%
“…Cycloheximide, as a eukaryote-specific inhibitor, has been commonly used in studying protozoan predation (Taylor & Pace, 1987). The most commonly used inhibitory concentration is 100 mg L À1 (Sanders & Porter, 1986), while various concentration ranges, for example 25-200 mg L À1 (Tremaine & Mills, 1987), were reported to be effective in inhibiting protozoa. Much higher concentrations of cycloheximide were used previously in sediment studies (Davies et al, 1995), presumably to counter the adsorption of cycloheximide by organic matter in sediment.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search yielded over 30 publications (most shown in Table 1), none of which tested all three assumptions thoroughly. Of the studies that did address these assumptions to some extent, most notable are Newell et al (1983), Sherr et al (1986), Taylor et al (1986), Taylor and Pace (1987), Tremaine and Mills (1987), and Tso and Taghon (2006) who evaluated the first and third assumptions in some detail, but only Taylor and Testing assumptions of the eukaryotic inhibitor method for investigating interactions between aquatic protozoa and bacteria, applied to marine sediment Pace (1987) also tested for effects on non-target eukaryotes (phytoplankton).…”
mentioning
confidence: 99%
“…McCambridge and McMeekin 1980;Newell et al 1983;Marino and Gannon 1991), whereas others reported incomplete inhibition (e.g. Sherr et al 1986;Sanders and Porter 1986;Taylor and Pace 1987;Tremaine and Mills 1987;Chabaud et al 2006). In some cases, cycloheximide took at least 48 h (Tremaine and Mills 1987) or even 3 d (Chabaud et al 2006) to inhibit protozoa, which is a problematic time frame for incubation experiments with natural communities.…”
mentioning
confidence: 99%
See 2 more Smart Citations